Vino viejo en botellas nuevas: un problema con la epistemología constructivista - Matthews, M. R. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1994)
This article deats with what the autor regards as a fatal epistemological error in the constructivist doctrine: its theory maintains the Aristotelian -empiricist epistemological paradigm. However, good constructivist pedagogy could be rescued from the deficient theory that parented it if we made a clear distinction between real and theoretical objects; and knowledge is recognised as a process of intellectual production working with real objects that have been described, apprehended, or incorporated by a theoretical object.